Is delayed ischemic preconditioning as effective on running performance during a 5 km time trial as acute IPC?. Issue 2 (February 2017) - Seeger, Joost P.H.; Timmers, Silvie; Ploegmakers, Danique J.M.; Cable, N. Timothy; Hopman, Maria T.E.; Thijssen, Dick H.J.
Abstract: Ischemic preconditioning (IPC) may enhance exercise performance. Cardioprotective effects of IPC are known to re-occur 24 h after the stimulus. Whether the delayed effect of IPC has similar effects as IPC on exercise performance is unknown. Objectives : Examine whether IPC applied 24 h (24-IPC) before exercise is equally effective as IPC in improving exercise performance. Design : Randomized, cross-over study Methods : 12 healthy participants were randomly exposed to SHAM-session, IPC or 24-IPC before a self-paced 5 km running trial on a treadmill. Subjects were blinded for time, speed and heart rate. Furthermore, heart rate, BORG, and the local tissue saturation index were measured during exercise, while lactate levels were determined after running. Using a regression model, we explored whether these parameters predicted the change in running time after IPC and 24-IPC. Results : We found no differences in finish time after IPC (SHAM: 1400 ± 105 s, IPC: 1381 ± 112 s, 24-IPC: 1385 ± 113 s; p  = 0.30). However, we observed a significant positive relation between the change in finish time after IPC and 24-IPC ( p  = 0.016; r  = 0.677). Using stepwise linear regression, a lower post-exercise blood lactate level after IPC or 24-IPC was significantly related to an improvement in finish time ( R 2  = 0.47, β  = -0.687, p  = 0.007). Conclusions : Although no significant effect of IPC or 24-IPC on exercise performance was found, individual finish time after IPC and 24-IPC were strongly correlated. Therefore, our data suggest that, at the individual level, the effects of 24-IPC are closely related to the effects of IPC.